HACCP: An Overview - Renee M. Goodrich; Keith R. Schneider; R. H. Schmidt (EDIS)
HACCP is a food safety management system that is increasingly utilized in all aspects of the food industry. The objectives of this fact sheet are to introduce the topic and to summarize the key components of a HACCP program.  This document is FSHN05-12, one of a series of the Food Science and Human Nutrition Department, UF/IFAS Extension. Original publication date August 2005.